Limitations of Authority the Prosecutor as Investigators in Taping on the Criminal act of Corruption - Juben MS Sagala; Azis Budianto (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims: (1) To find out the authority of the prosecutor as an investigator in wiretapping cases of criminal acts of corruption (2) To find out what are the obstacles for prosecutors in wiretapping cases of criminal acts of corruption. Researchers conducted research using an empirical normative approach, namely examining the implementation of written law in social life relations. Sources of data used in this study are primary data and secondary data. Methods of collecting data utilizing interviews (interviews) and literature/document studies. The data analysis method used in this research is qualitative analysis. The results of this study are expected to increase legal knowledge for students, academics, practitioners, and the public in general as well as researchers in particular regarding the prosecutor's more limited authority in the use of wiretapping devices, to conduct wiretapping must be approved by the court and the existence of other institutions authorized in the process of investigating corruption crime.